Carbon‐Based Electrocatalysts for Efficient Hydrogen Peroxide Production. Issue 49 (24th September 2021) - Bu, Yunfei; Wang, Yaobin; Han, Gao‐Feng; Zhao, Yunxia; Ge, Xinlei; Li, Feng; Zhang, Zhihui; Zhong, Qin; Baek, Jong‐Beom
Abstract: Hydrogen peroxide (H2 O2 ) is an environment‐friendly and efficient oxidant with a wide range of applications in different industries. Recently, the production of hydrogen peroxide through direct electrosynthesis has attracted widespread research attention, and has emerged as the most promising method to replace the traditional energy‐intensive multi‐step anthraquinone process. In ongoing efforts to achieve highly efficient large‐scale electrosynthesis of H2 O2, carbon‐based materials have been developed as 2e − oxygen reduction reaction catalysts, with the benefits of low cost, abundant availability, and optimal performance. This review comprehensively introduces the strategies for optimizing carbon‐based materials toward H2 O2 production, and the latest advances in carbon‐based hybrid catalysts. The active sites of the carbon‐based materials and the influence of coordination heteroatom doping on the selectivity of H2 O2 are extensively analyzed. In particular, the appropriate design of functional groups and understanding the effect of the electrolyte pH are expected to further improve the selective efficiency of producing H2 O2 via the oxygen reduction reaction. Methods for improving catalytic activity by interface engineering and reaction kinetics are summarized. Finally, the challenges carbon‐based catalysts face before they can be employed for commercial‐scale H2 O2 production are identified, and prospects for designing novel electrochemical reactors are proposed. Abstract : The latest advances in carbon‐based hybrid catalysts toward hydrogen peroxide (H2 O2 ) production are reviewed. In particular, the design of functional groups and the dependence of electrolyte pH play important roles to further improve the selectivity of H2 O2 production via the oxygen reduction reaction.